North-south syndrome, a complication of circulatory assistance with Veno-Arterial ECMO. A case report - Lazcano-Diaz, Emmanuel Adrián (2023)
We present the case of a 34-year-old male patient with a history of Marfan syndrome who was admitted to the emergency room for acute aortic regurgitation secondary to aneurysmal dilation of the ascending thoracic aorta. In the postoperative period, post-cardiotomy cardiogenic shock was documented, so circulatory support was initiated with peripheral Veno-Arterial ECMO, which developed hypoxemia due to bacterial pneumonia and data compatible with North-South syndrome. We present a review, non-conventional cannulation strategies and a diagnostic alternative for this entity.